Integrated Cascade Biorefinery Processes to Transform Woody Biomass Into Phenolic Monomers and Carbon Quantum Dots - Chen, Xue; Zhu, Jiubin; Song, Wenlu; Xiao, Ling-Ping (Frontiers in Bioengineering and Biotechnology, 2021)
A novel cascade biorefinery strategy towards phenolic monomers and carbon quantum dots (CQDs) is here proposed via coupling catalytic hydrogenolysis and hydrothermal treatment. Birch wood was firstly treated with catalytic hydrogenolysis to afford a high yield of monomeric phenols (44.6 wt%), in which 4-propanol guaiacol (10.2 wt%) and 4-propanol syringol (29.7 wt%) were identified as the two major phenolic products with 89% selectivity. An available carbohydrate pulp retaining 82.4% cellulose and 71.6% hemicellulose was also obtained simultaneously, which was further used for the synthesis of CQDs by a one-step hydrothermal process. The as-prepared CQDs exhibited excellent selectivity and detection limits for several heavy metal cations, especially for Fe3+ ions in an aqueous solution. Those cost-efficient CQDs showed great potential in fluorescent sensor in situ environmental analyses. These findings provide a promising path towards developing high-performance sensors on environmental monitoring and a new route for the high value-added utilization of lignocellulosic biomass.